2006
DOI: 10.1126/science.1119499
|View full text |Cite
|
Sign up to set email alerts
|

Flowers and Fungi Use Scents to Mimic Each Other

Abstract: Some flowering plants mimic the scent and appearance of mushroom fruiting bodies. Fungi may also mimic flowers. In addition, infection of plants by certain fungi can direct the plant to develop nonfunctional floral-like structures that nonetheless primarily serve the reproductive advantage of the fungus. These various mimicries may serve to attract insects that in turn spread fungal spores or plant pollen, thus facilitating sexual reproduction of the cryptic organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 9 publications
1
64
0
1
Order By: Relevance
“…While Dracula felix has little human-observable fragrance, D. lafleurii smells mushroom-like and mushroom fragrance compounds have been isolated from other Dracula species (Kaiser 2006). Flies approached D. lafleurii flowers with a seemingly scent-oriented flight (directly, in a spiral or in a zigzag pattern), and some hovered near the labellum before landing on it.…”
Section: Discussionmentioning
confidence: 99%
“…While Dracula felix has little human-observable fragrance, D. lafleurii smells mushroom-like and mushroom fragrance compounds have been isolated from other Dracula species (Kaiser 2006). Flies approached D. lafleurii flowers with a seemingly scent-oriented flight (directly, in a spiral or in a zigzag pattern), and some hovered near the labellum before landing on it.…”
Section: Discussionmentioning
confidence: 99%
“…1). With the help of a dominating floral lip that is imitating the lamellated cap of a fungus, the orchid triggers the female fungus fly to deposit its eggs in the fake mushroom cap, thereby pollinating the orchid (Kaiser 2006a) (Fig. 1).…”
Section: Natural Scentsmentioning
confidence: 99%
“…S1 for images of co-occurring mushrooms) (Vogel, 1978;Dentinger & Roy, 2010). Although previous studies have shown that some Dracula species produce the same volatile compounds that give mushrooms their characteristic odors (Kaiser, 1993(Kaiser, , 2006Policha, 2014), and that they are pollinated by mushroom-visiting drosophilid flies ( Fig. 1) (Endara et al, 2010;Policha, 2014), the relative importance of visual and olfactory floral traits to pollinator attraction remain unknown in this system.…”
Section: Introductionmentioning
confidence: 99%